POVERTY, UNEMPLOYMENT AND POVERTY ALLEVIATION/ERADICATION PROGRAMMES IN NIGERIA (1999-2004): AN APPRAISAL - Nwagwu, Ejikeme J. (University of Nigeria Journal of Political Economy, 2022)
This study critically evaluated poverty incidence and unemployment rate in Nigeria from 1999 to 2004; and the extent the poverty alleviation/eradication programmes affected the lives of the poor in Nigeria. The major objective of the poverty alleviation programme is to reduce absolute poverty among Nigerians. Contend analysis method was used to generate data for this study. The structural functional analysis exposed the defects of the structures and their zero-capacity to eradicate poverty and unemployment in Nigeria. The poverty alleviation programme has failed woefully to provide job opportunities for the teaming army of unemployed graduates; potable water; inadequate electricity, broad based development in education sector, poor healthcare delivery services and poor and faulty policies on agricultural development due to inconsistencies in her policies which are influenced mainly by political factors that serve the interest of the politicians. The benefits of the poverty alleviation programme missed the target population. The major problems of Nigeria is inconsistency in policies, lack of continuity of development projects, lack of vision and focus in policy formulation and execution, which have often led to serious contradictions. The government should review its policies to have functional education, agriculture, healthcare delivery services, transport system, employment opportunities and economy of the nation to move the country forward.